Extensional flow through microfabricated hyperbolic contractions - Mónica S. Neves Oliveira (2006)
Experiments and numerical simulations are used to investigate the extensionalflow through a 3-D planar hyperbolic micro-contraction. A converging geometry with aHencky strain of two was designed to produce a constant extensional rate along thecenterline. This configuration was used for the examination of Newtonian flows at low tomoderate Reynolds numbers and viscoelastic flows at low Deborah numbers. Numericalsimulations of the flow in the micro-contractions were obtained from a finite-volumemethod using non-orthogonal block-structured collocated meshes. The numerical resultsare compared to experimental measurements. For the base case of Newtonian flow, thenumerical predictions show good agreement with experiments. We also report preliminaryresults for a semi-dilute solution of polyethylene oxide.